17β-Oestradiol enhances the expansion and activation of myeloid-derived suppressor cells via signal transducer and activator of transcription (STAT)−3 signalling in human pregnancy. (13th April 2016) - Pan, T; Zhong, L; Wu, S; Cao, Y; Yang, Q; Cai, Z; Cai, X; Zhao, W; Ma, N; Zhang, W; Zhang, H; Zhou, J
Summary: During a successful pregnancy, the maternal immune system plays a critical role in maintaining immunotolerance towards semi-allogeneic fetal antigens. Recent studies have indicated that myeloid-derived suppressor cells (MDSCs) are active players in establishing fetal–maternal tolerance; however, the underlying mechanism remains poorly understood. In this study, we observed a significant expansion of monocytic MDSCs (M-MDSCs) in the peripheral blood of pregnant women, which suppressed T cell responses in a reactive oxygen species-dependent manner and required cell–cell contact. The number of M-MDSCs correlated positively with serum oestrogen and progesterone levels. Administration of 17β-oestradiol, but not progesterone, enhanced both the expansion and suppressive activity of M-MDSCs through signal transducer and activator of transcription (STAT)-3. Pretreatment with STAT-3 inhibitor JSI-124 almost completely abrogated the effects of 17β-oestradiol on MDSCs. Collectively, these results demonstrate that 17β-oestradiol-induced STAT-3 signalling plays an important role in both the expansion and activation of MDSCs during human pregnancy, which may benefit the development of novel therapeutic strategies for prevention of immune-related miscarriage.